Epidemiology of Vestibulo-Ocular Reflex Function: Data From the Baltimore Longitudinal Study of Aging. Issue 2 (February 2015) - Li, Carol; Layman, Andrew J.; Geary, Robert; Anson, Eric; Carey, John P.; Ferrucci, Luigi; Agrawal, Yuri
Abstract : Objective: To determine age-related changes in vestibulo-ocular reflex (VOR) function in community-dwelling adults, and evaluate these for associations with demographic characteristics and cardiovascular risk factors. Study Design: Cross-sectional analysis within the Baltimore Longitudinal Study of Aging (BLSA), a longitudinal prospective cohort study. Setting: Vestibular testing laboratory within an acute care teaching hospital. Patients: Community-dwelling adults enrolled in the BLSA. Intervention(s): Horizontal VOR gain measurement using video head-impulse testing and visual acuity testing. Main Outcome Measure(s): VOR gain was calculated as the ratio of eye velocity to head velocity. Demographic and cardiovascular risk factor data were collected through study questionnaires. Results: One hundred nine subjects were analyzed with mean age (SD) 69.9 years (14.2), with a range from 26 to 92 years. VOR gain remained stable from age 26 to 79 after which it significantly declined at a rate of 0.012/year ( p = 0.033) in adjusted analyses. Individuals aged 80 years or older had a nearly 8-fold increased odds of VOR gain less than 0.80 relative to those aged less than 80 years in multivariate models (prevalence of 13.2% vs. 2.8%; OR 7.79, 95% CI: 1.04–58.38). Otherwise, VOR gain did not differ significantly across demographic or cardiovascular risk groups. Conclusion: We report age-related decline in VOR function in individuals aged 80 years and older. Further analyses are in progress to establish the significance of these VOR abnormalities to functional and mobility outcomes in older individuals.